Obesity-Related Knee Osteoarthritis—Current Concepts - Russka Shumnalieva; Georgi Kotov; Simeon Monov (Life, 2023)
The knee is the joint most frequently involved in osteoarthritis and represents a significant contributor to patient morbidity and impaired functional status. Major risk factors include genetics, age, sex, mechanical load and obesity/metabolic syndrome. Recent studies highlighted the role of obesity and metabolic syndrome in the pathogenesis of knee osteoarthritis not simply through increased mechanical loading but the systemic effects of obesity-induced inflammation. The current concept of knee osteoarthritis is that of a ‘whole joint disease’, which highlights the involvement not only of articular cartilage but also the synovium, subchondral bone, ligaments and muscles. Obesity and metabolic syndrome are associated with higher levels of pro-inflammatory cytokines, increased production of adipokines with both protective and destructive effects on articular cartilage, an up-regulation of proteolytic enzymes such as matrix metalloproteinases and aggrecanases and an increase in free fatty acids and reactive oxygen species induced by dyslipidemia. These findings underscore that the adequate management of knee osteoarthritis needs to include an optimization of body weight and a beneficial mobility regimen. The possible introduction of pharmacological therapy targeting specific molecules involved in the pathogenesis of obesity-related osteoarthritis will likely also be considered in future therapeutic strategies, including personalized treatment approaches.